2022
DOI: 10.1007/s00259-022-05701-3
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of a CD44v6-targeted fluorescent agent for the detection of non-muscle invasive bladder cancer

Abstract: Bladder cancer is the fth most common malignancy in humans. Cystoscopy under white light imaging is the gold standard for bladder cancer diagnosis, but some tumors are di cult to visualize and can be overlooked, resulting in high recurrence rates. Method:We developed a phage display-derived peptide-based near-infrared imaging probe, PLSWT7-DMI, which binds speci cally to bladder cancer cells and is nontoxic to animals. Here, we report a clinical research of this probe for near-infrared uorescence endoscopic de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…CD44 is a cancer stem cell marker, which is highly expressed on the cell membrane of BCa and participates in cell adhesion, cell migration, tumor progression and metastasis ( 73 ). The results of the first human experiment showed that the fluorescence-guided imaging based on the NIR fluorescence probe targeting CD44v6 is a safe and effective method, which can improve the detection rate of BCa, and may enable complete resection to prevent recurrence ( 74 ). The pH-low insertion peptide (pHLIP) is a C-helix derived from the bacteriorhodopsin protein that targets the acidic microenvironment in the tumor matrix ( 75 ).…”
Section: Erbt Combined With Enhanced Imaging Technologymentioning
confidence: 99%
“…CD44 is a cancer stem cell marker, which is highly expressed on the cell membrane of BCa and participates in cell adhesion, cell migration, tumor progression and metastasis ( 73 ). The results of the first human experiment showed that the fluorescence-guided imaging based on the NIR fluorescence probe targeting CD44v6 is a safe and effective method, which can improve the detection rate of BCa, and may enable complete resection to prevent recurrence ( 74 ). The pH-low insertion peptide (pHLIP) is a C-helix derived from the bacteriorhodopsin protein that targets the acidic microenvironment in the tumor matrix ( 75 ).…”
Section: Erbt Combined With Enhanced Imaging Technologymentioning
confidence: 99%
“…There is an urgent need of precision surgery. We can foresee that the application of intraoperative FMI would be rapidly expanded [ 93 , 136 ]. So far, the clinical value of non-specific fluorophores has been widely explored.…”
Section: The Coming Future Of Precision Surgery In Chinamentioning
confidence: 99%
“…7 Preclinical experiments and clinical trials have been conducted based on the synthesis of peptides created with fluorescent phage display. 8–10 In a separate example from gastroenterology, molecular imaging with fluorescently labeled peptides has been developed to guide biopsy targeting high-grade dysplasia in Barrett's esophagus and to detect serrated colon polyps. 11–13…”
Section: Introductionmentioning
confidence: 99%
“…7 Preclinical experiments and clinical trials have been conducted based on the synthesis of peptides created with fluorescent phage display. [8][9][10] In a separate example from gastroenterology, molecular imaging with fluorescently labeled peptides has been developed to guide biopsy targeting high-grade dysplasia in Barrett's esophagus and to detect serrated colon polyps. [11][12][13] The leucine-rich G protein-coupled receptor 5 (LGR5) belongs to the glycoprotein receptor super-family, characterized by a large, leucine-rich extracellular domain and the peptide N-terminus.…”
Section: Introductionmentioning
confidence: 99%